Efficacy of topical ciprofloxacin and tobramycin in combination with dexamethasone in the treatment of chronic suppurative otitis media - Kaygusuz, Irfan; Karlidag, Turgut; Gök, Uzeyir; Yalçin, Sinasi; Keleş, Erol; Demirbag, Erhan; Kaygusuz, Türkkan Oztürk (My University, 2002)
OBJECTIVES: To evaluate the efficacy of topical ciprofloxacin and tobramycin with and without topical dexamethasone in the treatment of chronic suppurative otitis media without cholesteatoma. PATIENTS AND METHODS: The study included 103 ears of 80 patients (49 males, 31 females; mean age 31 years; range 18 to 60 years) with chronic suppurative otitis media without cholesteatoma. The patients were randomly divided into four groups to receive topical applications of either ciprofloxacin and tobramycin alone, or in combination with dexamethasone. Cultures were obtained from the ears preoperatively and 24 hours after treatment. RESULTS: Aerobic bacteria were isolated in 94.1% of patients before the treatment, the most common being Pseudomonas aeruginosa (38.9%). With dexamethasone, the clinical response for ciprofloxacin and tobramycin increased from 80% to 90% and from 70% to 75%, respectively, but this improvement was not significant (p > 0.03). Addition of dexamethasone to ciprofloxacin decreased the recovery period from 14 days to seven days, whereas no change (7 days) was observed with tobramycin. CONCLUSION: The efficacy of ciprofloxacin and tobramycin were similar in the treatment of chronic suppurative otitis media. Addition of dexamethasone to ciprofloxacin decreased the treatment period.
Kronik süpüratif otitis media tedavisinde topikal siprofloksasin ve tobramisinin deksametazon ile kullanimi.
Keywords: Administration, Topical; Adolescent; Adult; Anti-Bacterial Agents; Anti-Infective Agents; Anti-Inflammatory Agents; Chronic Disease; Ciprofloxacin; Dexamethasone; Drug Therapy, Combination; Female; Glucocorticoids; Humans; Male; Middle Aged; Otitis Media, Suppurative; Pseudomonas aeruginosa; Tobramycin; Treatment Outcome; antiinfective agent; antiinflammatory agent; ciprofloxacin; dexamethasone; glucocorticoid; tobramycin; adolescent; adult; article; chronic disease; clinical trial; controlled clinical trial; controlled study; drug combination; female; human; isolation and purification; male; microbiology; middle aged; pathology; Pseudomonas aeruginosa; randomized controlled trial; suppurative otitis media; topical drug administration; treatment outcome